Effectiveness of Organic Fertilizer Subsidies in Enhancing Profitability and Sustainability of Rice Farming: Evidence from West Sumatra, Indonesia - Hastarini Dwi Atmanti; Sri Rahayu Tri Astuti (CV. Get Press Indonesia, 2026)
Fertilizer subsidy policy has long been a central instrument of Indonesian agricultural policy, yet its effectiveness in improving farm profitability and long-term farming sustainability, particularly following the shift toward organic fertilizer subsidization, remains underexamined. This study analyzes the effectiveness of organic fertilizer subsidies and their impact on the profitability and sustainability of rice farming in Kabupaten Solok, West Sumatra, Indonesia. Using a comparative survey design, primary data were collected from 120 rice-farming households (60 subsidy recipients and 60 non-subsidized farmers) over one planting season. Subsidy effectiveness was evaluated using the five-rights framework; profitability was assessed through Revenue-Cost (R/C) and Benefit-Cost (B/C) ratio analysis; and sustainability was evaluated using a multidimensional Rapid Appraisal ordination index. A Cobb-Douglas production function with a subsidy-participation dummy variable was estimated to isolate the subsidy's contribution to output while controlling for land, seed, fertilizer, and labor inputs. Results indicate an overall subsidy effectiveness score of 74.3% (fairly effective), with right-place performing best and right-time weakest. The organic-subsidized group recorded significantly higher net farm income, R/C ratio, and sustainability index than the conventional group. Regression results confirmed a positive and significant effect of subsidy participation on rice output (coefficient = 0.076, p < 0.05). These findings support improved subsidy targeting and distribution scheduling to enhance profitability and long-term sustainability.